Evaluation of the Indian TrueNAT micro RT-PCR device with GeneXpert for case detection of pulmonary tuberculosis - Chaitali Nikam; Mubin Kazi; Chandrasekhar Nair; Majula Jaggannath; M Manoj; R Vinaya; Anjali Shetty; Camilla Rodrigues (International Journal of Mycobacteriology, 2014)
To evaluate the performance of TrueNAT (RT Micro PCR device) assay in comparison with GeneXpert on sputum samples from pulmonary cases of tuberculosis. 274 samples were processed to detect MTB by ZN smear examination, MGIT culture and molecular methods that included RT-PCR (ABI 7500 & TrueNAT) and GeneXpert for case detection of TB. The overall performance of the test with MGIT(Mycobacterium Growth Indicator Tube) culture as gold standard, sensitivity of smear, RT PCR/TrueNAT and Genexpert was 61.5% (CI:53.3–69.3%), 94.7% (CI:89.8–97.6%) & 96.0% (CI: 91.5–98.5%), respectively. Amongst the S+ (108) samples, RT-PCR/TrueNAT and GeneXpert showed a sensitivity of 99% (CI:94.9%–99.8%) and 100% (98.6%–100.0%), respectively. High concordance was observed between GeneXpert and TrueNAT for case detection of TB. The GeneXpert MTB/RIF test was independent on the user's skills. It has a short turn-around time and simultaneously detects RIF resistance with M. tuberculosis in less than 3 h. The TrueNAT MTB has good sensitivity and specificity in case detection with hands on time of less than 3 h as well as fits the requirements in resourcelimited health care settings. Larger, multi-site studies are required to obtain better estimates of the performance of TrueNAT MTB.